MAPPING A DECADE OF RESEARCH ON REFLECTIVE JOURNALS: IMPLICATIONS FOR MOTIVATION AND SELF-REGULATED LEARNING IN ELEMENTARY EDUCATION - Suti Suti; Edi Kurniawan; Bambang Subali; Nuni Widiarti (Universitas Islam Negeri Mataram, 2026)
This study aims to map and critically analyse research trends on reflective journals and their implications for learning motivation and self-regulated learning (SRL) in elementary education from 2015 to 2025. A hybrid approach combining systematic literature review and bibliometric analysis was employed, following PRISMA 2020 guidelines. Data were collected from Scopus, Web of Science, ERIC, and ScienceDirect, yielding 25 eligible empirical studies following a rigorous screening process. The findings reveal a significant increase in research on reflective journaling, with a shift from descriptive approaches toward process-oriented and experimental designs. Reflective journals demonstrate a strong and consistent impact on learning awareness, a moderate effect on SRL, and a variable influence on learning motivation. The results indicate that reflection serves as a metacognitive mechanism that indirectly influences motivation through self-regulatory processes. Additionally, instructional factors such as teacher feedback, structured prompts, and students’ literacy levels play a crucial role in determining effectiveness. This study proposes a conditional model of reflective learning, emphasising that the impact of reflective journals depends on contextual and pedagogical conditions. The findings help clarify conceptual relationships among reflection, SRL, and motivation and provide implications for instructional design and future research in elementary education.